2002
DOI: 10.1002/jsfa.1065
|View full text |Cite
|
Sign up to set email alerts
|

Sensory characterisation of ewe's milk cheeses using direct and indirect similarity measures: a comparison

Abstract: The purpose of the present study is to compare several direct and indirect (pro®le and hedonic scores) similarity measures. Moreover, the main relationships among assessors, sensory attributes and ewe's milk cheeses have been explored using different statistical techniques. For this purpose, visual inspection and correlation coef®cients among cheese sample sensory dimensions have been considered. All the solutions lead to very similar spatial con®gurations, except for preference data. In this case the consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The current study demonstrates the usefulness of a dissimilarity rating procedure to discriminate between products according to their overall odor differences and confirms the conclusion of a recent study (Barcenas et al, 2002). The use of this method enables an intuitive positioning of the samples in some psychological space, and contrasts with the complex task of odor profiling which implies 1) the decomposition of the overall space in an exhaustive set of independent and perceptually separable features (Lawless, 1999), 2) the choice of proper terms that precisely represent the odor for all panelists (Barcenas et al, 2002), and 3) the subjectivity of terms conceptualization. In addition, according to Lawless et al (1995), similarity data are thought to provide less experimenter influence and to be less constraining to subjects than data from attribute rating scales.…”
Section: Odor Assessment Of the Cheese Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study demonstrates the usefulness of a dissimilarity rating procedure to discriminate between products according to their overall odor differences and confirms the conclusion of a recent study (Barcenas et al, 2002). The use of this method enables an intuitive positioning of the samples in some psychological space, and contrasts with the complex task of odor profiling which implies 1) the decomposition of the overall space in an exhaustive set of independent and perceptually separable features (Lawless, 1999), 2) the choice of proper terms that precisely represent the odor for all panelists (Barcenas et al, 2002), and 3) the subjectivity of terms conceptualization. In addition, according to Lawless et al (1995), similarity data are thought to provide less experimenter influence and to be less constraining to subjects than data from attribute rating scales.…”
Section: Odor Assessment Of the Cheese Modelsupporting
confidence: 90%
“…Normed principal component analysis was performed on odor profile data. Direct dissimilarity assessment data were processed by MDS according to an alternative least squares algorithm (ALSCAL) described by Barcenas et al (2002). For all MDS mapping presented the stress value, which indicates how the data fitted the selected bidimensional solution, was lower than 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by Risvik et al (1997) if the individuals participating in an specific test are not screened considering an specific pattern, their responses would logically suppose also to be different. Barcenas et al (2002) recommend the use of statistical techniques accounting for individual variability, and suggested assessors should undergo specific training depending on the test to be performed in order to improve quality index.…”
Section: Consumer Versus Trained Panel Overall Comparisonmentioning
confidence: 99%
“…Previous studies(Barcenas, P erez Elortondo, Salmeron, & Albisu, 2002;Barcenas et al, 2003b) have pointed out the existence of high levels of individual Consumer repeatability assessment. INDSCAL bidimensional spatial configurations for the three replicates (A, B, C).…”
mentioning
confidence: 99%
“…Bidimensional INDSCAL solution obtained values for stress and RSQ of 0.17 and 0.89, respectively. RSQ value indicated that the first two dimensions explained 89% of the variability present within the data set, a percentage regularly considered as acceptable before choosing any specific spatial configuration (Ba´rcenas, Pe´rez Elortondo, Salmero´n & Albisu, 2002). In this line, Kruskal (1964) considered stress values below 0.2 as adequate.…”
Section: Interpanel Individual Differencesmentioning
confidence: 99%